2020
DOI: 10.1002/ange.201914661
|View full text |Cite
|
Sign up to set email alerts
|

Tetradentate Gold(III) Complexes as Thermally Activated Delayed Fluorescence (TADF) Emitters: Microwave‐Assisted Synthesis and High‐Performance OLEDs with Long Operational Lifetime

Abstract: Structurally robust tetradentate gold(III)‐emitters have potent material applications but are rare and unprecedented for those displaying thermally activated delayed fluorescence (TADF). Herein, a novel synthetic route leading to the preparation of highly emissive, charge‐neutral tetradentate [C^C^N^C] gold(III) complexes with 5‐5‐6‐membered chelate rings has been developed through microwave‐assisted C−H bond activation. These complexes show high thermal stability and with emission origin (3IL, 3ILCT, and TADF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…[34][35][36] Following our OLED studies on gold(III) systems, [34][35][36] Che and co-workers very recently reported tridentate and tetradentate ligand-containing gold(III) complexes that demonstrated EL performance and operational stability in vacuum-deposited OLEDs. [41][42][43] These small-molecular based gold(III) complexes were found to exhibit TADF properties, as supported by their fast radiative decay rate constant (k r ) in the order 10 5 s À1 , completely separated frontier orbitals, variable temperature emission and excited-state decay studies. It is worth noting that a large k r value of $1.36 Â 10 5 s À1 could also be found in our recently reported alkynylgold(III) dendrimers, 39 indicating that the emission is not purely originating from the triplet excited state.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…[34][35][36] Following our OLED studies on gold(III) systems, [34][35][36] Che and co-workers very recently reported tridentate and tetradentate ligand-containing gold(III) complexes that demonstrated EL performance and operational stability in vacuum-deposited OLEDs. [41][42][43] These small-molecular based gold(III) complexes were found to exhibit TADF properties, as supported by their fast radiative decay rate constant (k r ) in the order 10 5 s À1 , completely separated frontier orbitals, variable temperature emission and excited-state decay studies. It is worth noting that a large k r value of $1.36 Â 10 5 s À1 could also be found in our recently reported alkynylgold(III) dendrimers, 39 indicating that the emission is not purely originating from the triplet excited state.…”
Section: Introductionmentioning
confidence: 93%
“…It is worth noting that the excited state lifetimes of 1 are almost unchanged in the range of 200 K (1.3 ms) to 320 K (1.2 ms), suggesting that the thermal upconversion process is almost complete under these temperature conditions. 56 As the ISC rate constants (k ISC ) of structurally related cyclometalated gold(III) complexes are found to be in the picosecond regime, [41][42][43] much faster than that of the rate constant for uorescence decay (k  ), the DE ST of these complexes can be estimated by tting the variable-temperature emission data to the full kinetic model employed by Dias, Penfold, and Monkman. 57 1)) and k B is the Boltzmann constant.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Cu(I) complexes generally lack thermal and electrochemical stability, efforts have been directed to develop 2nd and 3rd row transition-metal-TADF emitters such as those of Pd(II), Ag(I), Au(I), and Au(III) to meet the stringent requirements of emitters for practical OLEDs (Li G. et al, 2019 ). Gratifyingly, high external quantum efficiencies (EQEs) of up to 27.5 and 25.0% have been achieved in OLEDs with Au(I) and Au(III) TADF emitters, respectively (Di et al, 2017 ; Zhou et al, 2020 ), reflecting Au-TADF emitters as an emerging new class of competitive, emissive dopant in OLED industry.…”
Section: Recent Advances In Metal-tadf Complexes and Their Applicatiomentioning
confidence: 99%
“…Solution-processed OLEDs fabricated with these emitters showed EQE of up to 11.1%. Che and co-workers developed new strategies for synthesizing tetradentate Au(III) complexes with O-bridged/spiro-arranged C ∧ C ∧ N ∧ C ligand by microwave induced C-H activation (Zhou et al, 2020 ). By rationally varying the substituent(s) on the ligand, the emissive excited states of the Au(III) emitters are changed from triplet intraligand ( 3 IL) excited states with k r of ~10 3 s −1 , to TADF from ILCT excited states.…”
Section: Recent Advances In Metal-tadf Complexes and Their Applicatiomentioning
confidence: 99%